Differentiated Learning in the Independent Curriculum: A Qualitative Analysis of Implementation Patterns and Challenges in Indonesian Elementary Education - Nurwahida Nurwahida; Yun Ratna Lagandesa; Sisriawan Lapasere; Rizal Rizal; Rangga Putera Boroallo (Papanda Publisher, 2026)
Differentiated learning is a central instructional approach promoted by Indonesia's Independent Curriculum (Kurikulum Merdeka) to address the diverse learning needs, readiness levels, and profiles of elementary school students. Despite its theoretical importance, the extent to which differentiated learning is implemented in practice remains poorly understood in specific school contexts. This study employed a descriptive qualitative design to examine the implementation of differentiated learning in grade IV at SD Inpres 3 Talise, Palu City, during the 2025/2026 academic year. Data were collected through classroom observations, semi-structured interviews, student questionnaires, and document analysis, and were analyzed using Miles and Huberman's interactive model. Findings reveal that process differentiation was the most consistently applied form, while content and product differentiation were largely absent and inconsistent. The composite student questionnaire score of 33.38% indicated a low level of perceived implementation. An unexpected finding showed that teachers spontaneously created inclusive and psychologically safe learning environments, suggesting an emergent environmental differentiation disposition. These findings reflect a theory–practice gap consistent with international literature and underscore the need for structured, practice-oriented professional development targeting content design and diversified assessment products to advance comprehensive differentiated learning under the Independent Curriculum.